Pengaruh Kecemasan Matematika terhadap Kemampuan Berpikir Kritis Matematis Siswa Kelas VII SMP Negeri 4 Bukittinggi - Nadira Safira; Risnawita; Aniswita; Tasnim Rahmat (YASIN, 2026)
Mathematical critical thinking skills are an essential competency in mathematics learning, but these skills remain relatively low, and studies examining the effect of mathematics anxiety on the mathematical critical thinking skills of junior high school students remain limited. This study aims to analyze the effect of mathematics anxiety on the mathematical critical thinking skills of seventh-grade students at SMP Negeri 4 Bukittinggi. The study employed a quantitative approach using an ex post facto research type and a correlational design. The research sample consisted of 43 students selected through simple random sampling. Data were collected using a mathematics anxiety questionnaire and a mathematical critical thinking skills test that met the validity and reliability requirements. The data were analyzed using descriptive and inferential statistics through simple linear regression with the assistance of IBM SPSS Statistics. The results show that mathematics anxiety has a negative effect on students’ mathematical critical thinking skills, with a regression coefficient of −0.326 and a correlation coefficient of −0.304. The coefficient of determination of 10.49% indicates that mathematics anxiety contributes 10.49% to the variation in students’ mathematical critical thinking skills, while the remainder is influenced by other factors not examined in this study. These findings strengthen the empirical evidence regarding the role of affective factors in mathematics learning and affirm that students’ psychological conditions also influence the development of higher-order thinking skills. This study implies the importance of teachers creating a supportive learning environment and implementing strategies that can reduce mathematics anxiety so that students’ mathematical critical thinking skills can develop optimally.